Multi-parametric MRI techniques for the non-invasive assessment of patients with liver disease - Pavlides, M (2015)
Liver disease is a major worldwide health problem with high prevalence and poor patient outcomes. In the last decade, efforts to improve liver disease severity assessment have led to the development of many non-invasive methods, including magnetic resonance (MR) techniques. The overarching aim of this thesis was to examine a multi-parametric MR technique in the evaluation of different aspects of liver disease. The MR protocol included T1 and T2* mapping techniques which were used to compute the iron corrected T1 (cT1) and the liver inflammation and fibrosis (LIF) score as measures of liver inflammation and fibrosis. In healthy volunteers, it was found that premenopausal women had a higher median liver cT1 (784ms) compared to postmenopausal women (741ms; p=0.038) or age matched men (742ms; p=0.005). Furthermore, blood volume was identified as the most significant physiological determinant of liver cT1 and a correction algorithm was developed to compute the "volume adjusted and iron corrected T1" (vacT1), which removes the confounding effect of liver congestion and improves the performance of the test as a biomarker of liver fibrosis. Against histology, liver cT1 was strongly associated with liver collagen proportionate area, particularly in patients with viral hepatitis (r=0.80; p<0.0001). Furthermore, liver cT1 / LIF had an excellent diagnostic accuracy for the assessment of multiple aspects of non-alcoholic fatty liver disease (NAFLD) with an area under the receiver operating curve of 0.89 for the identification of significant NAFLD. In the evaluation of portal hypertension, liver cT1 (r=0.49; p=0.038) was associated with the hepatic vein pressure gradient (HVPG), and spleen cT1 was identified as a new biomarker of portal pressure (r=0.66; p<0.0001 vs HVPG). Furthermore, liver cT1 / LIF was shown to be useful in predicting clinical outcomes, with a negative predictive value of 100% for a LIF<2. Overall, this thesis demonstrated multi-parametric MR to be a robust technique that can assess the whole spectrum of liver disease.